THE USE OF FINANCIAL DERIVATIVES IN MEASURING BANK RISK MANAGEMENT EFFICIENCY: A DATA ENVELOPMENT ANALYSIS APPROACH - Shahsuzan Zakaria (Asian Academy of Management Journal, 2017)
As risk-taking is an essential part of the banking industry, it is important for banks to practice efficient risk management to ensure survival in uncertain climates, such as the Asian Financial Crisis of 1997. Due to banking operations being specifically affected by fluctuations in interest rates, which cause financial imbalances, banks are now required to put in place an effective management structure that incorporates risk management efficiency measures that help mitigate the wide range of risks they face. Such efficient risk management measures are paramount in building robust and sound financial systems. This study provides a new approach for measuring risk management efficiency levels in banks by offering a more detailed insight into the data envelopment analysis (DEA) approach based on the usage of a financial risk instrument. Comparatively, the results of this study confirm the findings by Hahn (2008) indicating that Japanese banks are superior in terms of managerial efficiency when compared to European and US banks. Risk management efficiency measurement contributes to the strengthening of the efficiency levels of banking risk management and the achievement of sound risk management in banking operations, thus underscoring the impact of derivative usage on banking risk management efficiency.